A expans??o internacional dos bancos brasileiros: motiva????es, restri????es e perspectivas - Pajares, Fernando Marcial Roncal (2010)
The globalization of the economy is one of the main driving forces of the internationalization of organizations. This phenomenon has been studied extensively in the academic literature of Management and Economics, generating many studies and explanatory theories. The increased presence of global companies in manufacturing sectors was followed by several theoretical studies that attempted to explain this process. But the same does not occur with the internationalization of the services sector, specifically banking. The international banking activity has increased significantly over the last four decades. This overseas movement is also seen as a defensive strategy, necessary to ensure continuity of business with companies that have foreign subsidiaries. Although there are large Brazilian banks with high rates of profitability, they do not have a significant international presence. Having as the theoretical framework the Internalization, OLI and Uppsala theories we studied the main reasons for the internationalization of the largest Brazilian banks (Banco do Brasil, Ita??-Unibanco and Bradesco), and discussed their presence in international markets. The results show that the main reasons are to follow their multinational clients and to obtain resources to finance local projects.